Close relation between the integrating factor and the Green function for first-order differential equations - de Castro, Antonio S. [UNESP] (FapUNIFESP (SciELO), 2023)
For first-order ordinary differential equations, it is shown by a very simple and straightforward approach how the integral representation of the particular solution with the integrating factor as part of the integrand can be manipulated in favor of an integral representation in terms of the Green function.
Íntima relação entre o fator integrante e a função de Green para equações diferenciais de primeira ordem
Keywords: Green function; Integrating factor; Linear velocity-dependent friction